First record of Oligobregma Kudenov & Blake, 1975 (Annelida: Polychaeta: Scalibregmatidae Malmgren, 1867) from Brazil with the description of three new species - Mendes, Samuel Lucas Da Silva Delgado; Paiva, Paulo Cesar De; Rizzo, Alexandra E. (Zootaxa, 2024)
Oligobregma represents the most speciose genus of Scalibregmatidae with 17 valid species. Most of them occur at great depths and are found living on soft bottoms. Here, we present the descriptions of O. nonatoi sp. nov., O. cruzae sp. nov., and O. bakkeni sp. nov., sampled from the Brazilian continental shelf and slope, and a key to all species of Oligobregma. O. nonatoi sp. nov. differs from its congeners by the presence of a triangular prostomium with short rounded horns, acicular spines on notopodia of chaetigers 1–4 and on neuropodia of chaetigers 1–3. Oligobregma cruzae sp. nov. can be distinguished by the presence of a quadrangular prostomium with two short, rounded horns, acicular spines on chaetigers 1–4, and lyrate chaetae from chaetiger 5. Finally, O. bakkeni sp. nov. is unique among its congeners by the presence of acicular spines with rounded tips. This is the first record of this genus along the Brazilian coast and the specimens were collected on Espírito Santo, Campos and Santos sedimentary basins, both located in Brazilian southeast region. The sampling campaigns were carried out in scientific expeditions related to two research projects: “Santos Project – Santos Basin Environmental Characterization” and “Ambes Project – Espírito Santo Basin Assessment Project”, both coordinated by CENPES/PETROBRAS.